Video Games and English Learning: An Exploratory Study of EFL Pre-Service Teachers’ Perceptions - Díaz Larenas, Claudio (2023)
The present study explores the knowledge and perceptions that 72 Chilean EFL (English as a foreign language) pre-service teachers have regarding the effect of video games in their daily and academic routine in terms of foreign language learning. By applying a 5-point Likert scale, it was possible to gather data concerning their sociodemographic characteristics and their views in relation to five dimensions: (1) Generalexperience with video games, (2) general preferences about video games, (3) strengths and weaknesses of video games, (4) video games as a learning experience, and (5) video games and the four language skills. Once the data were collected, the Spearman’s orrelation coefficient was used with the purpose of determining the relationships among the respondents’ answers. The results indicated that the four language skills, especially the receptive skills, can be practiced while playing video games. Also, digital games allowed the participants to teach and learn from other players through gameplay. This process was followed by a hierarchical cluster analysis that allocated the respondents into four groups based on the similarities of their responses.